Efektywność wytwarzania w rolnictwie polskim i w rolnictwie nowych krajów członkowskich Unii Europejskiej z Europy Środkowej i Wschodniej - Baer-Nawrocka, Agnieszka; Kiryluk, Ewa (Effectiveness of Agriculture in Poland and in the Other New EU Member States from Central and Eastern Europe, 2006)
The paper attempts to assess productivity of agriculture in analyzed countries. An assessment was held using partial productivity of labour, land and capital. In order to assess the differentiation of the production factors productivity among countries, the values of synthetic coefficients of productivity, were calculated, using Hellwig method. The analysis proves that effectiveness of Polish agriculture is lower not only compared to the EU-15 countries but also compared to the some of the new EU member states. The main disadvantage in Polish agriculture is the low labour productivity.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 1, s. 44-50